2011
DOI: 10.1371/journal.pntd.0001297
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Trypanosomatid Pathogens to PI3/mTOR Kinase Inhibitors Affords a New Opportunity for Drug Repurposing

Abstract: BackgroundTarget repurposing utilizes knowledge of “druggable” targets obtained in one organism and exploits this information to pursue new potential drug targets in other organisms. Here we describe such studies to evaluate whether inhibitors targeting the kinase domain of the mammalian Target of Rapamycin (mTOR) and human phosphoinositide-3-kinases (PI3Ks) show promise against the kinetoplastid parasites Trypanosoma brucei, T. cruzi, Leishmania major, and L. donovani. The genomes of trypanosomatids encode at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 68 publications
3
74
0
Order By: Relevance
“…S7A). Multiple studies have reported that high doses of NVP-BEZ235 resulted in weight loss in mouse models (31,32). After 4 weeks of treatment, NVP-BEZ235 reduced mouse body weight in a dose-dependent manner (Supplementary Fig.…”
Section: Dht Reduces Side Effects During Nvp-bez235 Treatmentmentioning
confidence: 95%
“…S7A). Multiple studies have reported that high doses of NVP-BEZ235 resulted in weight loss in mouse models (31,32). After 4 weeks of treatment, NVP-BEZ235 reduced mouse body weight in a dose-dependent manner (Supplementary Fig.…”
Section: Dht Reduces Side Effects During Nvp-bez235 Treatmentmentioning
confidence: 95%
“…During assay development, final experimental conditions were assessed in terms of DMSO and compound concentration, inoculum density and resazurin-dependent fluorescence, and validated with standard trypanocidal drugs and kinase inhibitors 14,28]. The selected compounds from the GSK collection were tested at 4 mM concentration in a single point assay to test their growth inhibition in a log-phase culture of T. b. brucei using the optimized assay conditions.…”
Section: High-throughput Screeningmentioning
confidence: 99%
“…These target families include phosphodiesterases 11], histone deacetylases 12], and kinases 13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The protozoacidal activity of the analogues was found to be highly 25 dependent on a 4-hydroxyl group at the 6-aryl ring, and a chiral 1-phenylethanamine substituent in posi- 26 tion 4. Further, the potency was affected by the aromatic substitution pattern of the phenylethanamine: 27 the unsubstituted, the meta-fluoro and the para-bromo substituted derivatives had the lowest minimum 28 protozoacidal concentrations (8)(9)(10)(11)(12)(13)(14)(15)(16) lg/mL). Surprisingly, both enantiomers were found to have high 29 potency suggesting that this compound class could have several modes of action.…”
mentioning
confidence: 99%